WEB-BASED MANAGEMENT OF GOODS DEMAND APPLICATIONS IN THE NUSANTARA FRACTION OF THE OFFICE OF THE DPRD NORTH SUMATRA - Fitriani, Fitriani; Suhardi, Suhardi (Journal of Information Systems and Technology Research, 2022)
The Nusantara Faction is a combination of several parties, namely the United Development Party (PPP), Perindo Party and the National Awakening Party (PKB) which are in charge of running the government. The Nusantara Faction is in the government office of the North Sumatra Province Regional House of Representatives (DPRD-SU). In order to carry out their duties smoothly, the Nusantara Faction requires work goods and equipment. The system for managing demand for goods in the Nusantara Faction is still carried out conventionally, namely data for managing demand for goods still uses paper. The current system still has a shortage of inputting data for managing demand for goods, causing quite a long time. The goal to be achieved is to make it easier for staff who work in the Nusantara Faction in carrying out and managing requests for goods in the Nusantara Faction can be run online. So it is necessary to have a web-based goods demand management application which is expected to be able to overcome the problems that occur in the Nusantara Faction. With this application, it can make it easier to input data for managing demand for goods and provide solutions to overcome problems during the process of inputting data for managing demand for goods.